Measurement of time-dependent CP asymmetries in B0 → D(*)±π± decays and constraints on sin(2β + γ) - Aubert, B; Barate, R; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
The CP-violating asymmetries in fully reconstructed B0 → D(*)∓π∓ decays and constraints on sin(2β + γ) were investigated. The time evolution of decays was sensitive to γ because of interference between the Cabibbo-Kobayashi-Maskawa (CKM) favored decay and doubly CKM-suppressed decay. The consistency of data was computed with given value of sin(2β + γ) by counting fraction of simulated experiments for which χ 2(sin(2β + γ))-χmin2 was smaller. The lower limit on |sin(2β + γ)| was observed at 68% confidence level which drops from 0.69 to 0.60.